A composite solder, its preparation method and application
By premixing and adding Ni/Al2O3 in step-by-step Ni/Al2O3 and then ultrasonic melting casting molding method, the problem of the increase in melting temperature and the decrease in wettability of the low-silver solder is solved after the Ag element content decreases, and the high strength and toughness of the composite solder is achieved, reducing production costs.
Patent Information
- Application Number
- CN202411875687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
After reducing the Ag element content, the existing low-silver lead-free solder increases the melting temperature and the wettability decrease, resulting in an increase in production costs and a decrease in process performance.
By premixing, Ni/Al2O3 is added in step by step and then ultrasonic melting casting to create molding method, Ni/Al2O3 is evenly dispersed into the solder matrix Sn1.0Ag0.5Cu, thereby improving the toughness and strength of the composite solder.
The high strength and toughness of composite brazing materials are achieved, the production cost is reduced, and good wetting and process performance are maintained.
Smart Images

Figure CN119328359B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material engineering, and in particular to a composite solder and a preparation method and application thereof. Background Art
[0002] Traditional Sn-Pb alloys once occupied an important position in the field of welding and were widely used because of their low melting point and excellent wettability. However, in recent years, as people's understanding of lead toxicity has deepened, it has been found that lead can cause harm to human tissues, nerves, and blood, which greatly limits the application scope of Sn-Pb alloys in welding. Based on this situation, many scholars have turned their research direction to the field of lead-free solders. Among all kinds of lead-free solders, tin-based solders are the main research objects. Among them, typical binary lead-free solders include Sn-Ag system, Sn-Cu system, Sn-Zn system, Sn-Bi system, and Sn-In system. Among typical ternary lead-free solders, Sn-Ag-Cu alloys are the most widely used. SnAgCu solder has become the first choice to replace Sn-Pb solder due to its good wettability, relatively excellent mechanical properties and excellent fatigue resistance. Among the SnAgCu series lead-free solders, Sn-3.0Ag-0.5Cu recommended by the Japan Electronics and Information Technology Industry Association, Sn-3.8Ag-0.7Cu recommended by the European Union, and Sn-3.9Ag-0.6Cu recommended by the National Electronic Equipment Manufacturing Association of the United States have attracted much attention. However, these three solders have a common problem, that is, the content of Ag element is too high, which will inevitably lead to an increase in the production cost of the solder.
[0003] In order to better meet the needs of the market, developing a low-silver lead-free solder that meets the performance requirements and reduces costs has become a hot topic of research at home and abroad. However, with the reduction of Ag content, many problems have also been brought to SnAgCu solder, such as increased melting temperature and significantly reduced process performance such as wettability. The selected reinforcement phase Al2O3 is a common ceramic nanoparticle. Compared with the existing literature, the composite solder prepared by adding Al2O3 as a reinforcement phase has the largest increase in strength percentage compared with the solder matrix before and after stretching. Wu et al. added a certain amount of α-Al2O3 to the low-silver solder Sn0.3Ag0.7Cu, which greatly improved the shear force of the brazed joint. However, the wettability of the composite solder will decrease after directly adding Al2O3, so Al2O3 needs to be surface treated. Ni can smooth the concentration gradient and enhance wettability, so it is possible to consider coating the Al2O3 surface with a Ni layer (denoted as Ni / Al2O3). However, the density of Ni / Al2O3 is very different from that of the solder matrix, and it is usually difficult to add it directly into the solder matrix. Summary of the invention
[0004] To solve the above problems, the purpose of the present invention is to provide a new composite solder and its preparation method and application, and successfully add Ni / Al2O3 into the solder matrix Sn1.0Ag0.5Cu (denoted as SAC105).
[0005] In the preparation process of composite solder, the Ni / Al2O3 powder reinforcement phase needs to be evenly dispersed into the matrix solder matrix SAC105. Since the density of Ni / Al2O3 is much smaller than that of the solder matrix powder SAC105, segregation is prone to occur. In order to make the two mixed more evenly, the present invention adopts a pre-mixed step-by-step addition of Ni / Al2O3 and then ultrasonic melting and casting molding method.
[0006] The preparation method of the composite solder of the present invention specifically comprises the following steps:
[0007] (1) Preparation of Ni / Al2O3 powder;
[0008] (2) Take Sn1.0Ag0.5Cu powder as the solder matrix powder, divide it into 5 parts by mass, each of which is recorded as powder A, then take the Ni / Al2O3 powder obtained in step (1), premix the Ni / Al2O3 powder with one part of powder A, and divide the premixed powder into 4 parts by mass, each of which is recorded as powder B;
[0009] (3) Take another portion of powder A and place it in a crucible. Then add flux paste to the crucible and heat it to melt. After melting, remove the surface slag. Then add a portion of powder B to the crucible and perform an ultrasonic treatment. After the ultrasonic treatment, add another portion of powder A and perform an ultrasonic treatment again. After the ultrasonic treatment, add another portion of powder B and perform an ultrasonic treatment again. According to the above method, add powder A and powder B alternately in sequence, and perform an ultrasonic treatment after each addition of powder A or powder B. Finally, add four portions of powder B and the remaining three portions of powder A alternately to the crucible to obtain a molten liquid C. The molten liquid C is quickly cast into a stainless steel mold, cooled and demolded to obtain a Ni / Al2O3 reinforced Sn1.0Ag0.5Cu composite solder.
[0010] Furthermore, in step (1), Ni / Al2O3 powder is prepared by chemical plating;
[0011] Furthermore, the Ni / Al2O3 powder is prepared in step (1) by the following method: 1 g Ni(NO3)2•6H2O and 0.27 g NaOH (i.e., the molar ratio of Ni(NO3)2•6H2O to NaOH is 1:2) are added to 80 mL distilled water, stirred magnetically until completely dissolved, and then 0.5 g Al2O3 (i.e., the mass ratio of Al2O3 to Ni(NO3)2•6H2O is 1:2), continue to stir fully until mixed evenly to obtain a mixed solution A; then weigh a hydrazine hydrate solution with a mass fraction of 80%, wherein the molar ratio of hydrazine hydrate to the above-mentioned Ni(NO3)2•6H2O is 1:1, and add the hydrazine hydrate solution to the mixed solution A three times in small amounts each time, stirring while adding, and stir fully after the complete addition to obtain a mixed solution B, transfer the mixed solution B to a 100mL reactor, react at 80°C for 7h, centrifuge and wash the solution in the reactor, discard the upper liquid, wash the lower precipitate with deionized water, and then keep the obtained solid in a tubular furnace at 500°C for 2h under an argon atmosphere to obtain Ni / Al2O3 powder;
[0012] Furthermore, the mass of the Ni / Al2O3 powder in step (2) is 0.05% to 0.5% of the mass of the solder matrix powder (i.e. Sn1.0Ag0.5Cu);
[0013] Furthermore, the premixing in step (2) is specifically performed by rolling and stirring on a roller mill for 2 hours, with a ball-to-material ratio of 3:1.
[0014] Furthermore, the model of the soldering paste in step (3) is OM340.
[0015] Furthermore, in step (3), the mass of the soldering solder paste accounts for 10% of the mass of the powder A.
[0016] Furthermore, in step (3), the duration of each ultrasound treatment was 90 s and the ultrasound power was 80 W.
[0017] Furthermore, in step (3), the molten liquid C is quickly cast into a stainless steel mold having a size of 70 mm × 10 mm × 10 mm in length × width × height;
[0018] The present invention also aims to provide a composite solder prepared according to the above method and the application of the composite solder in electronic components.
[0019] The preparation method of the present invention is a pre-mixing and step-by-step addition of Ni / Al2O3 followed by ultrasonic melting and casting. When preparing the composite solder, since the density of Ni / Al2O3 is much smaller than that of the matrix, it is necessary to accurately control the addition amount, addition sequence, ultrasonic time and other parameters to ensure uniform mixing of the components.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The toughness of the composite solder can be increased by pre-mixing and adding Ni / Al2O3 in steps and then ultrasonic melting and casting. The previous powder metallurgy method can improve the strength of the composite solder, but the powder metallurgy products are relatively brittle and the toughness will decrease. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of the Ni / Al2O3-enhanced Sn1.0Ag0.5Cu composite solder according to an embodiment of the present invention;
[0023] Figure 2 It is a mechanical property diagram of the Sn1.0Ag0.5Cu composite solder reinforced with different doping amounts of Ni / Al2O3 in Examples 1-4 and the Sn1.0Ag0.5Cu solder prepared in Comparative Example 1, where a is the tensile strength; b is the elongation;
[0024] Figure 3 It is the SEM image of the Ni / Al2O3 enhanced Sn1.0Ag0.5Cu composite solder prepared in Example 3, wherein Figure (a) is the SEM image, Figure (b) is the full spectrum, Figure (c) is the Ag element, Figure (d) is the Al element, Figure (e) is the O element, Figure (f) is the Ni element, Figure (g) is the Cu element, and Figure (h) is the EDS spectrum. DETAILED DESCRIPTION
[0025] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.
[0026] Examples 1-4 and Comparative Example 1 systematically studied the microstructural evolution and strengthening mechanism of the composite solder by comparing the organization and performance analysis of the reinforcement phase with different addition amounts.
[0027] Embodiment 1:
[0028] (1) Preparation of Ni / Al2O3
[0029] Ni / Al2O3 was prepared by chemical plating. Specifically, 1 g Ni(NO3)2•6H2O and 0.27 g NaOH (i.e., the molar ratio of Ni(NO3)2•6H2O to NaOH was 1:2) were added to 80 mL of distilled water, stirred magnetically until completely dissolved, and then 0.5 g Al2O3 (i.e., the mass ratio of Al2O3 to Ni(NO3)2•6H2O is 1:2), continue to stir fully until mixed evenly to obtain a mixed solution A; then weigh a hydrazine hydrate solution with a mass fraction of 80%, wherein the molar ratio of hydrazine hydrate to the above-mentioned Ni(NO3)2•6H2O is 1:1, and add the hydrazine hydrate solution to the mixed solution A three times in small amounts each time, stirring while adding, and stir fully after the complete addition to obtain a mixed solution B, transfer the mixed solution B to a 100mL reactor, react at 80°C for 7h, centrifuge and wash the solution in the reactor, discard the upper liquid, wash the lower precipitate with deionized water, and then keep the obtained solid in a tubular furnace at 500°C for 2h under an argon atmosphere to obtain Ni / Al2O3 powder;
[0030] (2) 90 g of commercial SAC105 powder was taken as solder matrix powder, and the powder was divided into 5 parts by weight, each of which was recorded as powder A. 0.045 g of the Ni / Al2O3 powder obtained in step (1) was taken, and the Ni / Al2O3 powder was premixed with one part of powder A, specifically, the powder was rolled and stirred on a roller mill for 2 hours, with a ball-to-powder ratio of 3:1. After the stirring was completed, the premixed powder was divided into 4 parts by weight, each of which was recorded as powder B.
[0031] (3) Take another portion of powder A, pour it into the crucible, and then add model OM340 solder paste to heat and melt. The mass of the solder paste is 10% of the mass of powder A. After melting, use a spoon to scrape off the slag on the surface. Then add a portion of powder B to the crucible and perform the first ultrasonic wave. After the first ultrasonic wave, add another portion of powder A and perform the second ultrasonic wave. After the second ultrasonic wave, add another portion of powder B and perform the third ultrasonic wave. According to the above method, after the third ultrasonic wave, add powder A and powder B alternately in turn, and perform an ultrasonic wave after each addition of powder A or powder B. The duration of each ultrasonic wave is 90s, and the ultrasonic power is 80W. This can make the density The small Ni / Al2O3 reinforcement phase is better dispersed in the local range; in summary, four parts of powder B and the remaining three parts of powder A are added alternately to the molten liquid of powder A mixed with solder paste in the crucible. After each addition of the material (i.e., powder A or powder B), the ultrasonic power is 80W for 90 seconds. After the last ultrasonic treatment, the molten liquid C is obtained. The molten liquid C is quickly cast into a stainless steel mold with a size of 70mm×10mm×10mm (length×width×height). After cooling and demolding, a Ni / Al2O3-enhanced Sn1.0Ag0.5Cu composite solder ingot is obtained, in which the mass fraction of Ni / Al2O3 is 0.05wt.%. The schematic diagram of the preparation process of the Ni / Al2O3-enhanced Sn1.0Ag0.5Cu composite solder is shown in the figure. Figure 1 shown.
[0032] Embodiment 2:
[0033] (1) Preparation of Ni / Al2O3
[0034] Step (1) in this embodiment is the same as step (1) in Embodiment 1;
[0035] (2) 90 g of commercial SAC105 powder was taken as solder matrix powder, and the powder was divided into 5 parts by weight, each of which was recorded as powder A. 0.09 g of Ni / Al2O3 powder obtained in step (1) was taken, and the Ni / Al2O3 powder was premixed with one part of powder A, specifically, the powder was rolled and stirred on a roller mill for 2 hours, with a ball-to-powder ratio of 3:1. After the stirring was completed, the premixed powder was divided into 4 parts by weight, each of which was recorded as powder B.
[0036] (3) Take another portion of powder A, pour it into the crucible, add OM340 solder paste and heat to melt. The mass of the solder paste is 10% of the mass of powder A. After melting, use a spoon to scrape off the slag on the surface. Then add a portion of powder B to the crucible and perform the first ultrasonic treatment. After the first ultrasonic treatment, add another portion of powder A and perform the second ultrasonic treatment. After the second ultrasonic treatment, add another portion of powder B and perform the third ultrasonic treatment. According to the above method, after the third ultrasonic treatment, add powder A and powder B alternately in sequence, and perform an ultrasonic treatment each time after adding powder A or powder B. The ultrasonic treatment time for each ultrasonic treatment is 90 seconds, and the ultrasonic power is 80W. In this way, the Ni / Al2O3 reinforcement phase with low density can be better dispersed in a local area; in summary, four parts of powder B and the remaining three parts of powder A are alternately added to the molten liquid of powder A mixed with solder paste in the crucible, and ultrasonic power of 80 W is used for 90 seconds after each addition of the material. After the last ultrasonic treatment, molten liquid C is obtained, and the molten liquid C is quickly cast into a stainless steel mold with a size of 70 mm×10 mm×10 mm (length×width×height), cooled and demolded to obtain a Ni / Al2O3 reinforced Sn1.0Ag0.5Cu composite solder ingot, in which the mass fraction of Ni / Al2O3 is 0.1wt.%.
[0037] Embodiment 3:
[0038] (1) Preparation of Ni / Al2O3
[0039] Step (1) in this embodiment is the same as step (1) in Embodiment 1;
[0040] (2) 90 g of commercial SAC105 powder was taken as solder matrix powder, and the powder was divided into 5 parts by weight, each of which was recorded as powder A. 0.27 g of Ni / Al2O3 powder obtained in step (1) was taken, and the Ni / Al2O3 powder was premixed with one part of powder A, specifically, the powder was rolled and stirred on a roller mill for 2 hours, with a ball-to-powder ratio of 3:1. After the stirring was completed, the premixed powder was divided into 4 parts by weight, each of which was recorded as powder B.
[0041] (3) Take another portion of powder A, pour it into the crucible, add OM340 solder paste and heat to melt. The mass of the solder paste is 10% of the mass of powder A. After melting, use a spoon to scrape off the slag on the surface. Then add a portion of powder B to the crucible and perform the first ultrasonic treatment. After the first ultrasonic treatment, add another portion of powder A and perform the second ultrasonic treatment. After the second ultrasonic treatment, add another portion of powder B and perform the third ultrasonic treatment. According to the above method, after the third ultrasonic treatment, add powder A and powder B alternately in sequence, and perform an ultrasonic treatment each time after adding powder A or powder B. The ultrasonic treatment time for each ultrasonic treatment is 90 seconds, and the ultrasonic power is 80W. In this way, the Ni / Al2O3 reinforcement phase with low density can be better dispersed in a local area; in summary, four parts of powder B and the remaining three parts of powder A are alternately added to the molten liquid of powder A mixed with solder paste in the crucible, and ultrasonic power of 80 W is used for 90 seconds after each addition of the material. After the last ultrasonic treatment, molten liquid C is obtained, and the molten liquid C is quickly cast into a stainless steel mold with a size of 70 mm×10 mm×10 mm (length×width×height), cooled and demolded to obtain a Ni / Al2O3 reinforced Sn1.0Ag0.5Cu composite solder ingot, wherein the mass fraction of Ni / Al2O3 is 0.3wt.%.
[0042] Embodiment 4:
[0043] (1) Preparation of Ni / Al2O3
[0044] Step (1) in this embodiment is the same as step (1) in Embodiment 1;
[0045] (2) 90 g of commercial SAC105 powder was taken as solder matrix powder, and the powder was divided into 5 parts by weight, each of which was recorded as powder A. 0.45 g of the Ni / Al2O3 powder obtained in step (1) was taken, and the Ni / Al2O3 powder was premixed with one part of powder A, specifically, the powder was rolled and stirred on a roller mill for 2 hours, with a ball-to-powder ratio of 3:1. After the stirring was completed, the premixed powder was divided into 4 parts by weight, each of which was recorded as powder B.
[0046] (3) Take another portion of powder A, pour it into the crucible, add OM340 solder paste and heat to melt. The mass of the solder paste is 10% of the mass of powder A. After melting, use a spoon to scrape off the slag on the surface. Then add a portion of powder B to the crucible and perform the first ultrasonic treatment. After the first ultrasonic treatment, add another portion of powder A and perform the second ultrasonic treatment. After the second ultrasonic treatment, add another portion of powder B and perform the third ultrasonic treatment. According to the above method, after the third ultrasonic treatment, add powder A and powder B alternately in sequence, and perform an ultrasonic treatment each time after adding powder A or powder B. The ultrasonic treatment time for each ultrasonic treatment is 90 seconds, and the ultrasonic power is 80W. In this way, the Ni / Al2O3 reinforcement phase with low density can be better dispersed in a local area; in summary, four parts of powder B and the remaining three parts of powder A are alternately added to the molten liquid of powder A mixed with solder paste in the crucible, and ultrasonic power of 80 W is used for 90 seconds after each addition of the material. After the last ultrasonic treatment, molten liquid C is obtained, and the molten liquid C is quickly cast into a stainless steel mold with a size of 70 mm×10 mm×10 mm (length×width×height), cooled and demolded to obtain a Ni / Al2O3 reinforced Sn1.0Ag0.5Cu composite solder ingot, wherein the mass fraction of Ni / Al2O3 is 0.5wt.%.
[0047] Comparative Example 1:
[0048] (1) Take 90g of commercial solder matrix SAC105 powder;
[0049] (2) Add the solder matrix SAC105 powder of step (1) into a crucible, and then add the solder paste of model OM340 and heat to melt. The mass of the solder paste is 10% of the mass of the solder matrix SAC105 powder. After melting, scrape the surface slag with a spoon, and then quickly cast it into a stainless steel mold with a size of 70mm×10mm×10mm (length×width×height). Cool and demold, and obtain a Sn1.0Ag0.5Cu solder ingot.
[0050] from Figure 2 It can be seen that with the increase of the doping amount of the reinforcing phase Ni / Al2O3, the tensile strength and elongation first increase and then decrease, but the tensile strength and elongation of the composite solder prepared in Examples 1-4 are significantly greater than the Sn1.0Ag0.5Cu solder matrix prepared in Comparative Example 1. The tensile strength and elongation of the Sn1.0Ag0.5Cu solder matrix prepared in Comparative Example 1 are 30MPa and 25%, respectively. When the doping amount reaches 0.3wt.%, the tensile strength and elongation reach 36MPa and 29%, respectively. This is 20% and 16% higher than the values of the Sn1.0Ag0.5Cu solder matrix prepared in Comparative Example 1, respectively.
[0051] Figure 3This is a SEM image of the composite solder structure with a mass fraction of 0.3wt.% of Ni / Al2O3 prepared in Example 3. Figure 3 It can be seen that the added Ni / Al2O3 is dispersed in the solder matrix SAC105.
[0052] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite solder, characterized in that: The specific steps include: (1) Ni / Al2O3 powder was prepared by chemical plating as follows: First, 1g Ni(NO3)2•6H2O and 0.27g NaOH were added to 80mL distilled water respectively, and magnetic stirring was performed until they were completely dissolved. Then, 0.5g Al2O3 was added and stirred thoroughly until the mixture was uniformly mixed to obtain a mixed solution A. Then, a hydrazine hydrate solution with a mass fraction of 80% was weighed, wherein the molar ratio of hydrazine hydrate to the above Ni(NO3)2•6H2O was 1:
1. The hydrazine hydrate solution was added to the mixed solution A in small amounts three times each time, and stirred while adding. After the solution was completely added, the solution was stirred thoroughly to obtain a mixed solution B. The mixed solution B was transferred to a 100mL reactor, reacted at 80°C for 7h, and then the solution in the reactor was centrifuged and washed, the upper liquid was discarded, and the lower precipitate was washed with deionized water. Then, the obtained solid was kept warm in a tubular furnace at 500°C for 2h under an argon atmosphere to obtain a Ni / Al2O3 powder. (2) Take Sn1.0Ag0.5Cu powder as the solder matrix powder, divide it into 5 parts by mass, each of which is recorded as powder A, then take the Ni / Al2O3 powder obtained in step (1), premix the Ni / Al2O3 powder with one part of powder A, and divide the premixed powder into 4 parts by mass, each of which is recorded as powder B, wherein the mass of Ni / Al2O3 powder is 0.05% to 0.5% of the mass of the solder matrix powder; (3) Take another portion of powder A and place it in a crucible. Then add solder paste to the crucible and heat it to melt. The model of the solder paste is OM340, and the mass of the solder paste accounts for 10% of the mass of powder A. After melting, remove the surface slag. Then add a portion of powder B to the crucible and perform an ultrasonic treatment. After the ultrasonic treatment, add another portion of powder A and perform an ultrasonic treatment again. After the ultrasonic treatment, add another portion of powder B and perform an ultrasonic treatment again. According to the above method, add powder A and powder B alternately in sequence, and perform an ultrasonic treatment after each addition of powder A or powder B. Finally, add four portions of powder B and the remaining three portions of powder A alternately to the crucible to obtain a molten liquid C. The molten liquid C is quickly cast into a stainless steel mold, cooled and demolded to obtain a Ni / Al2O3 reinforced Sn1.0Ag0.5Cu composite solder.
2. The method for preparing the composite solder according to claim 1, characterized in that: The premixing in step (2) is specifically performed by rolling and stirring on a roller mill for 2 hours, with a ball-to-material ratio of 3:
1.
3. The method for preparing the composite solder according to claim 1, characterized in that: In step (3), each ultrasonic treatment lasted for 90 seconds and the ultrasonic power was 80 W.
4. The method for preparing the composite solder according to claim 1, characterized in that: In step (3), the molten liquid C is rapidly cast into a stainless steel mold with dimensions of 70 mm x 10 mm x 10 mm in length x width x height.
5. The composite solder obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the composite solder as claimed in claim 5 in electronic components.
Citation Information
Patent Citations
High-performance tin-based solder alloy and preparation method thereof
CN102513720A
Nano particle homodisperse aluminum base intermediate, preparation method and application method
CN110669902A